What Makes People Hide Knowledge? Influence of Passive Leadership and Creative Self-Efficacy - Mubarak, Namra; Osmadi, Atasya; Khan, Jabran; Mahdiyar, Amir; Riaz, Asim (Frontiers in Psychology, 2021)
Although numerous studies have been conducted in the field of knowledge sharing with focus given to its importance, but very little attention has been given to knowledge hiding practices. Very few studies have been found making an attempt to figure out its impact and antecedents. Likewise, negative role of passive leadership in project management literature has not been evidenced enough despite of its existence in project-based organizations. Both knowledge hiding and passive leadership are highly neglected areas in project management literature. Therefore, the present study not only attempts to investigate the influence of passive leadership on knowledge hiding, but it also aimed to explore the role of creative self-efficacy between them. IT project organizations were chosen in order to collect the data because of their high failure rate due to insufficient knowledge transfer. The findings of the study revealed that neglected passive leadership greatly influences the knowledge hiding practices among individuals. However, according to the results, knowledge hiding practices reduce in the presence of creative self-efficacy. Thus, the antecedents of knowledge hiding should be considered in order to create an innovative and successful business environment. The results are highly significant not only for the field of project management, but also for other practitioners.